2017
DOI: 10.1038/s41598-017-03995-0
|View full text |Cite
|
Sign up to set email alerts
|

Protecting visual short-term memory during maintenance: Attentional modulation of target and distractor representations

Abstract: In the presence of distraction, attentional filtering is a key predictor of efficient information storage in visual short-term memory (VSTM). Yet, the role of attention in distractor filtering, and the extent to which attentional filtering continues to protect information during post-perceptual stages of VSTM, remains largely unknown. In the current study, we investigated the role of spatial attention in distractor filtering during VSTM encoding and maintenance. Participants performed a change detection task w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…Accordingly, the findings from Fukuda and Vogel (), along with the findings from the current study, suggest that the filtering mechanism in general seems to be determined very early in the processing stream. While most of the studies on WM investigate its capacity storage component, in recent years there has been a growing literature demonstrating the importance of controlling what enters WM in determining performance (Allen, Baddeley, & Hitch, ; Feldmann‐Wüstefeld & Vogel, ; Robison & Unsworth, ; Unsworth & Robison, ; Vissers, Gulbinaite, van den Bos, & Slagter, ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the findings from Fukuda and Vogel (), along with the findings from the current study, suggest that the filtering mechanism in general seems to be determined very early in the processing stream. While most of the studies on WM investigate its capacity storage component, in recent years there has been a growing literature demonstrating the importance of controlling what enters WM in determining performance (Allen, Baddeley, & Hitch, ; Feldmann‐Wüstefeld & Vogel, ; Robison & Unsworth, ; Unsworth & Robison, ; Vissers, Gulbinaite, van den Bos, & Slagter, ).…”
Section: Discussionmentioning
confidence: 99%
“…Won et al, 2016), and SSVEPs are overall robust using a wide array of frequencies (at least 1 to 50 Hz; Herrmann, 2001;Zhu et al, 2010). However, some spatial attention studies have found no attentional modulation of SSVEPs in the beta band (Antonov et al, 2020;Gulbinaite et al, 2019), or have found effects only for the second harmonic of beta band frequencies (Garcia et al, 2013;Kim et al, 2007;Vissers et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Given that some work has reported significant effects only for the second harmonic (e.g., Kim et al, 2007;Vissers et al, 2017), we likewise examined SSVEP amplitude at 48 Hz and 60 Hz, with the caveat that the 60 Hz harmonic is contaminated by line noise (Appendices I and J). We found no significant attention effects for either second harmonic frequency.…”
Section: Non-pre-registered Control Analysesmentioning
confidence: 99%
“…In consequence, amplitude reductions would indicate that neuronal resources are utilised in a more efficient way. Thus, the meditation-specific pattern of improved MOT performance in conjunction with reduced SSVEP amplitudes is likely to result from an increased ability to ignore irrelevant distractors or to quickly disengage from them, preserving only relevant items in visual short-term memory 39 . It is likely to reflect efficiency gains that results from the training of interacting brain networks of attention during meditation which transfers to generalised improvements of attentional functions without meditation 21 , 25 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, evidence from cognitive neuroscience demonstrates the close interplay between attention and working memory, highlighting the important role of selective attention in encoding information in working memory 37 , 38 . In addition, the efficiency of allocating attentional resources to goal-relevant rather than irrelevant, distracting information predicts working memory performance 39 . Fukuda and Vogel 40 demonstrate that the ability to rapidly disengage from distracting information is an important contributor to high-capacity working memory performance.…”
Section: Introductionmentioning
confidence: 99%